Inhibition of AKT with the Orally Active Allosteric AKT Inhibitor, MK-2206, Sensitizes Endometrial Cancer Cells to Progestin - Pant, Alok (Public Library of Science, 2012)
Progestin resistance is a major obstacle to treating early stage, well-differentiated endometrial cancer as well as recurrent endometrial cancer. The mechanism behind the suboptimal response to progestin is not well understood. The PTEN tumor suppressor gene is frequently mutated in type I endometrial cancers and this mutation results in hyperactivation of the PI3K/AKT pathway. We hypothesized that increased activation of AKT promotes an inadequate response to progestins in endometrial cancer cells. Ishikawa cells stably transfected with progesterone receptor B (PRB23 cells) were treated with the AKT inhibitor, MK-2206, which effectively decreased levels of p(Ser473)-AKT in a dose-dependent (10 nM to 1 uM) and time-dependent manner (0.5 h to 24 h). MK-2206 inhibited levels of p(Thr308)-AKT and a downstream target, p(Thr246)-PRAS40, but did not change levels of p(Thr202/Tyr204)ERK or p(Thr13/Tyr185)SAPK/JNK, demonstrating specificity of MK-2206 for AKT. Additionally, MK-2206 treatment of PRB23 cells resulted in a significant increase in levels of progesterone receptor B (PRB) protein. Microarray analysis of PRB23 cells identified PDK4 as the most highly upregulated gene among 70 upregulated genes in response to R5020. Inhibition of AKT further upregulated progestin-mediated expression of PDK4 but did not affect another progestin-responsive gene, SGK1. Treatment of PRB23 cells with R5020 and MK-2206 independently decreased viability of cells while the combination of R5020 and MK-2206 caused the greatest decrease in cell viability. Furthermore, mice with xenografted tumors treated with MK-2206 alone or with progesterone alone exhibited modest reductions in their tumor volume. The largest decrease in tumor size was observed in the mice treated with both MK-2206 and progesterone; these tumors exhibited the least proliferation (Ki67) and the most apoptosis (cleaved caspase-3) of all the treatment groups. In summary, inhibition of AKT stabilizes the Progesterone Receptor B and augments progesterone response in endometrial cancer cells that have hyperactivated AKT.